Persepsi Perilaku Kesehatan Pekerja Pengangkut Sampah pada Masa New Normal di Surabaya - Effendi, Masitah (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2022)
This study aims to determine the perception of the health behavior of garbage man during the new normal. Researchers want to see how garbage man perform healthy behavior, starting from disease prevention, healing disease when sick, seeking and using health services. This study uses a qualitative research method because the researcher intends to describe the perception of health behavior of garbage man in the new normal period by using the health behavior theory of Becker. In this study, the informants were workers who transported garbage in Surabaya. The results of the study stated that the health behavior carried out by the garbage man when he felt symptoms of pain, he would use his perception of the pain he felt, then consider various possible advantages and disadvantages of the treatment action to be taken in order to make the right decision in carrying out the treatment. action so that the body returns to health.